3D printing and freeze casting hierarchical mxene pressure sensor - Hao Wang; Jun Wang; Jie Tao; Kai Jin; Yuxin Li (Nanocomposites)
Although MXene sheets are highly conductive, it is still challenging to prepare MXene complex functional materials for flexible electronics by simple and effective methods. In 3D printing, especially direct ink writing (DIW), different materials are used to create complex 3D shapes by formulating inks with controlled rheological properties. Herein, a printable MXene ink is developed, exhibiting good rheological properties, to print different complex shapes, and potentially manufacture electronic devices such as sensors. Then, we fabricated a highly sensitive hierarchical structure MXene composite materials composed of two layers of bionic micro-spine microstructure and network structure, formed by 3D printing and freeze casting. The obtained MXene composite materials exhibit good pressuring sensing properties with a sensitivity of 17.5 kPa−1, a fast response time (<100 ms), and excellent cycle stability exceeding 10,000 cycles. The sensing mechanism suggesting that the hierarchical structure can effectively improve the sensitivity and response time. It also has good potential application in the monitoring of human health activities, including the detection of human joint activities, walking, pressure distribution, and other sports.